Vergence Formula for Estimating the Refractive Status of Aphakic Eyes in Pediatric Patients - Tian, Linlu; Zhao, Peiquan; Zhu, Huang; Kang, Xiaoli; Wei, Yan; Chen, Luya; Li, Jing (Frontiers in Medicine, 2022)
Clinical relevance: A vergence formula may facilitate the simple and reliable estimation of the refractive status of aphakic eyes. Background: Measuring the refractive error of paediatric eyes with aphakia is difficult. This study investigated the accuracy and applicability of a vergence formula for estimating the refractive status of such eyes. Methods: A retrospective review of the medical records, created between January 2016 and December 2018, of paediatric patients with aphakia was conducted. A vergence formula, based on axial length, was used to calculate the refractive status of the aphakic eyes. The refractive values determined using retinoscopy, an automatic refractometer, and the vergence formula were compared. Results: A total of 72 eyes (47 patients) were analysed. The spherical equivalents of the refractive errors (mean ± standard deviation) of the eyes were determined using retinoscopy (13.01 ± 3.27 D), automatic refractometry (12.90 ± 3.23 D), and the vergence formula (12.70 ± 3.4 D). The correlation coefficient between retinoscopy values determined using retinoscopy and the vergence formula, automatic refractometry and the vergence formula, and retinoscopy and automatic refractometry were 0.968, 0.987, and 0.979, respectively. The Bland-Altman consistency analysis revealed that the mean differences in the spherical equivalent values between retinoscopy and automatic refractometry, retinoscopy and the vergence formula, and automatic refractometry and the vergence formula were 0.11 D, 0.31 D, and 0.21 D, respectively, with 95% limits of agreement of -1.20 to 1.41 D, -1.37 to 2.00 D, and -0.90 to 1.31 D, respectively. Conclusion: The vergence formula was effective for evaluating the refractive status of aphakic eyes in paediatric patients.